PREPARING TEACHERS TO ORGANIZE DIALOGIC LEARNING OF STUDENTS: COMMUNICATIVE ASPECT - Budnyk, Olena; Fomin, Kateryna; Novoselska, Nadiia; Voitovych, Anna (Revista Inclusiones, 2020)
The article presents the results of the theoretical analysis of the problem of organizing educational dialogue with students and the teacher’s ability to implement communicative activities effectively. The importance of methods of problem-based learning is substantiated, which stimulates students to active communicative interaction, cooperation and co-creation. Methods of research: survey, testing, pedagogical experiment (N = 294), methods of pedagogical statistics. The experiment revealed the level of communicative readiness of future elementary school teachers to organize a classroom dialogue. These indicators were analyzed in the control (CG) and experimental (EG) groups. The results of the study show that after the experiment 34.4% of the EG students expressed a high level of communicative readiness for organizing pupil’ dialogic learning (before the experiment only 18.3% of students expressed this intention, dynamics + 16.1%); the average level is 49.5% of respondents (dynamics +6.2). At the same time the proportion of low-level students decreased by 22.3% and the proportion of respondents with this level was 16.1% at the end of the experiment (compared to 31.3% in the CG). This is the evidence of the effectiveness of the developed and tested methodological support (tools) for improving the effectiveness of communicative training of future teachers for the organization of dialogic learning.